1994
DOI: 10.1016/0270-9139(94)90176-7
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder sludge: Spontaneous course and incidence of complications in patients without stones

Abstract: Although the ultrasonic detection of gallbladder sludge is relatively frequent, its clinical importance remains unclear, partly because of the paucity of reliable investigations regarding its natural course in patients without stones. In a retrospective study we investigated the course and clinical significance of gallbladder sludge in patients without stones or other identified gallbladder abnormalities. The diagnosis of gallbladder sludge was made by ultrasound scan in 286 (1.7%) of 17,021 patients. The mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…If the sludge persists—for example, because the patient has already had several pregnancies or is receiving total parenteral nutrition—gall stones can form 6. Most patients with biliary sludge have no symptoms, but the sludge itself can cause acute cholecystitis.…”
Section: Pathogenesismentioning
confidence: 99%
“…If the sludge persists—for example, because the patient has already had several pregnancies or is receiving total parenteral nutrition—gall stones can form 6. Most patients with biliary sludge have no symptoms, but the sludge itself can cause acute cholecystitis.…”
Section: Pathogenesismentioning
confidence: 99%
“…The prevalence of biliary sludge in all of our patients was 4%, a figure similar to that previously reported in three other large series: 20 cases among 2,067 Danish unselected patients,15 121 of 1806 ultrasound studies performed for abdominal pain,2 and 286 of 17,021 consecutive ultrasound examinations. 16 Cirrhosis was not mentioned in these studies, but the other causes we found were regularly observed: biliary obstruction, malignant diseases, acute pancreatitis, and all conditions predisposing to altered bile composition and/or gallbladder stasis. In these studies, the apparently low prevalence of gallbladder sludge might be explained either by the detection limit of ultrasonography or by the fluctuating and reversible course of sludge over a long time span.3 Studies are in progress in our department to define more precisely the risk factors and the natural history of biliary sludge in cirrhotic patients.…”
Section: Discussionmentioning
confidence: 79%
“…Consequently, our data suggest that second harmonic imaging could be useful, in the future, in patients with biliary sludge for both diagnosis and follow‐up. This second aspect may be even more relevant, as accurate follow‐up is necessary in some subjects in order to evaluate the progression towards gallstones, 32 and to determine the effect of medical treatments on biliary sludge and the prevention of its more dramatic clinical expressions 8 . Nevertheless, before firm conclusions can be drawn, studies on larger series of patients are necessary to clearly assess the role of second harmonic imaging in biliary sludge detection.…”
Section: Discussionmentioning
confidence: 99%
“…The chemical composition is variable, although it is most commonly composed of cholesterol monohydrate crystals, calcium bilirubinate granules, other calcium salts and gall‐bladder mucus 3 . Clinically, its course may be characterized by spontaneous resolution, long‐term persistence or progression to gallstones 4–7 . The persistence of biliary sludge may be asymptomatic, or responsible for biliary colic in about 10% of patients and acalculous cholecystitis or acute pancreatitis in a smaller percentage 8–10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation